EMBEDDING CRITICAL THINKING THROUGH CRITICAL READING: TEACHING NARRATIVE TEXT IN JUNIOR HIGH SCHOOL - Ajeng Meidina Fadhillah (Journal of English and Education, 2017)
This article reports a research on embedding critical thinking through critical reading in teaching narrative text to junior high school students. The research was aimed to find out whether or not critical reading strategies can improve students’ critical thinking skills and how critical reading strategies help students to think critically in reading narrative text. Thirty five of eight graders in one of junior high schools in West Bandung were involved in this study. This study employed mixed methods as the methodology. The data were gained through pre-test, post-test, classroom observation and interview. The findings revealed that there were 18 of 35 students (51%) who made a high improvement of their critical thinking skills. It means that critical reading strategies were considered could improve students’ critical thinking skills in reading narrative text. In addition, the five critical reading strategies as proposed by Sousa (2004) and Winston Salem State University (2013) namely previewing, outlining and summarizing, reflecting and evaluating were proven to have its own role in fostering students’ critical thinking skills. Moreover, students critical thinking evolvement were investigated and listed from the most evident to the least evident; 1) reasoning, 2) predicting, 3) recognising context and 4) questioning.